2022
DOI: 10.1097/md.0000000000029266
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and non-gastrointestinal complication rates associated with diagnostic esophagogastroduodenoscopy under sedation

Abstract: Esophagogastroduodenoscopy (EGD) under sedation may result in gastrointestinal (GI) and non-GI complications. However, no previous studies have reported 30-day GI and non-GI complications after diagnostic EGD under sedation.We conducted a retrospective, observational study of 30-day GI and non-GI complication rates after outpatient diagnostic EGD under sedation in subjects ≥18 years between January 2012 and December 2017 based on a common data model database. Thirty-day complication rates were compared with EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…conducting sedation by a non-anaesthesiologist) should only be done with optimal characteristics of the sedative, like minimal associated risks and low profile of adverse events, short recovery time, potent anxiolytic/analgesic effects, and a predictable pharmacokinetic profile. It should be noted that some studies also validated the safety of practicing sedation by non-anaesthesiologists with drugs like propofol [ 15 , 147 ]. Further studies also demonstrated the safety and efficacy of propofol-related sedation conducted by physicians and trained nurses for upper gastrointestinal endoscopic procedures [ 127 , 148 150 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…conducting sedation by a non-anaesthesiologist) should only be done with optimal characteristics of the sedative, like minimal associated risks and low profile of adverse events, short recovery time, potent anxiolytic/analgesic effects, and a predictable pharmacokinetic profile. It should be noted that some studies also validated the safety of practicing sedation by non-anaesthesiologists with drugs like propofol [ 15 , 147 ]. Further studies also demonstrated the safety and efficacy of propofol-related sedation conducted by physicians and trained nurses for upper gastrointestinal endoscopic procedures [ 127 , 148 150 ].…”
Section: Methodsmentioning
confidence: 99%
“…An increased risk of developing these complications is observed among patients with comorbidities, and the incidence does not usually differ between non-anaesthetist and anaesthetist clinicians. Various complications have been reported, mainly bronchopulmonary aspiration, vasovagal events, arrhythmia, hypotension, and hypoxaemia [13][14][15][16]. Among the different complications, estimates indicate that cardiopulmonary complications are the most serious and common.…”
Section: Safety and Adverse Eventsmentioning
confidence: 99%
“…Although surveillance EGD is generally regarded as safe, EGD itself or the use of sedative agents during EGD has some potential to cause adverse events. 8 - 10 Particularly, cardio-cerebrovascular (CCV) adverse events following EGD may be responsible for a majority of the mortality. In a nationwide survey study in the United States, the risk of cardiac adverse events was one of the main considerations for clinicians in deciding whether to use sedative agents during EGD.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Several studies have reported CCV adverse events following diagnostic EGD in the average-risk population. 8 , 9 , 12 , 13 However, data on CCV adverse events following surveillance EGD in patients with GC have not been reported. Therefore, we aimed to investigate the incidence of CCV adverse events, including cardiac and cerebral adverse events, arterial thromboembolism (ATE), and pulmonary embolism (PE), after surveillance EGD with or without sedation in patients with GC.…”
Section: Introductionmentioning
confidence: 99%